Self-Efficacy Analysis of EFL Student with Digital Game Experiences - Muhammad Najmussaqib Diya Alhaq; Nur Arifah Drajati; M. Sri Samiati Tarjana (Universitas Lampung, 2020)
The English lessons in the school curricula are designed to be a benchmark of student foreign language competency measurement. To succeed in every single aspect of the lesson, students need to enhance their will and motivation so they can fulfill all the needs and complete it. Self-efficacy is one of the most critical factors which can sustain student academic intention amongst all. Thus, the role of experience is one of the factors which can keep a prominent way of developing functional self-efficacy. As a form of experience, playing a video game (also known as gaming behavior) is the one who considered valuable in hoisting the effectiveness of student's English learning, especially in developing the existence of student's self-efficacy. Some students in different stages of formal education schools like elementary, and senior high scholars with different specifications toward the experience and the characteristics of self-efficacy will be the object of this research. Using a descriptive qualitative approach, six students from a different grade and school are analyzed and proved in having self-efficacy toward English lesson. This thing implies that students that have some experiences in playing digital games are provided with self-efficacy and appears more dominant than the students without such experiences. http://dx.doi.org/10.23960/aksara/v21i1.pp17-32